A discursive analysis of Hijab removal: Identity and piety - Fitria Sari Yunianti (IJISH (International Journal of Islamic Studies and Humanities), 2022)
To veil and wear a proper dress are among the commands of Allah to Muslim women, stipulated in several verses in the Quran. The term hijab or jilbab is the most important term related to that issue. In Indonesia, wearing a hijab is identical to Muslim women’s identity and reflects their piety. However, when one decides to unveil, the negative stigma is unavoidable. This article examines women’s perception of the Quran on veiling command based on two aspects. To begin with, the women’s understanding of the encouragement of wearing hijab and the women’s perception of the verses after deciding to put off their veil. In this study, the theory of religious piety and identity is applied as a conceptual framework and discursive analysis as a method of analysis. This study will present a discursive analysis of women’s understanding of the veiling concept. Particularly on their motivation for wearing hijab, veiling experience, and unveiling reason.